2022
DOI: 10.1186/s12935-022-02693-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of inhibitor of growth (ING) family members in health and malignancy

Abstract: ING genes belong to family of tumor suppressor genes with regulatory functions on cell proliferation, apoptosis, and cellular senescence. These include a family of proteins with 5 members (ING1-5), which are downregulated in human malignancies and/or affected by pathogenic mutations. ING proteins are highly evolutionarily conserved proteins containing several domains through which bind to chromatin structures by exerting their effects as readers of histone modification marks, and also binding to proteins like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported that ING3 expression varies in different types of cancer. Almost all in vitro studies have shown that ING3 has the ability to inhibit growth ( 47 ), however, it was found that ING3 can function as an oncogene in prostate cancer ( 30 ). Nabbi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ING3 expression varies in different types of cancer. Almost all in vitro studies have shown that ING3 has the ability to inhibit growth ( 47 ), however, it was found that ING3 can function as an oncogene in prostate cancer ( 30 ). Nabbi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The ING gene belongs to the tumour-suppressor gene family and has regulatory functions in cell proliferation, apoptosis and cell senescence ( 16 ). This family includes five members (ING1-5) that enhance p53 activity by inducing acetylation or increasing its stability ( 17 ). ING1 has been demonstrated to be a tumour suppressor in a variety of human cancers, including lung cancer ( 18 ), colorectal cancer ( 19 ), and prostate cancer ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…ING (Inhibitor of Growth) proteins are vital in cellular functions, bridging histone acetylation activities with chromatin through their conserved region of PHD ( Taheri et al, 2022 ). The PHD mediates interactions with methylated lysine residues in ING proteins, playing a crucial role in gene expression regulation and DNA damage response in cancer biology ( Jacquet and Binda, 2021 ).…”
Section: Introductionmentioning
confidence: 99%